An early-strength, low-shrinkage inert back-wall grouting material and preparation method thereof

By using iron desulfurization slag ultrafine powder and other materials in tunnel construction to form sulfur aluminate gelling system and ettringite crystals, the problem of insufficient shrinkage of inert grouting materials is solved, and early strength, low shrinkage and high The grouting material with compressive strength improves construction stability and material applicability.

CN116217184BActive Publication Date: 2024-12-27CHINA RAILWAY TUNNEL GROUP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211651532.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-21
Publication Date
2024-12-27
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

In tunnel construction, the compensation shrinkage capacity of inert grouting materials is insufficient, resulting in the loss of effective bonding between the grouting materials and the rock wall, affecting the construction stability, and the addition of bentonite will reduce the strength.

Method used

The early-strength and low-shrinkage inert wall grouting material consisting of ultrafine powder of iron desulfurization slag, fly ash, diatomaceous earth, enhanced alkaline exciters, desulfurization gypsum, etc., is used to form sulfur aluminate glue The condensed system and ettringite crystals improve the early strength and compactness of the grouting material and reduce shrinkage.

Benefits of technology

The low shrinkage, short set time and high compressive strength of the grouting material are achieved, and the problems of poor shrinkage and insufficient strength of the inert slurry are overcome, and the stability of construction and the applicability of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004010884400000151
    Figure BDA0004010884400000151
  • Figure BDA0004010884400000161
    Figure BDA0004010884400000161
Patent Text Reader

Abstract

The invention discloses an early-strength, low-shrinkage inert wall back-grouting material and a preparation method thereof, which is composed of the following raw materials by weight: 16% to 22% of hot metal desulfurization slag ultrafine powder, 2.1% to 2.3% of modifier, 5% to 11% of fly ash, 0.4% to 0.6% of water reducer, 3% to 5% of enhanced alkaline activator, 30% to 34% of river sand, 24% to 28% of water, 0.3% to 0.4% of reinforcing agent, 3% to 6% of desulfurized gypsum, 2% to 5% of diatomaceous earth, and the total content of the raw materials is 100%. The inert wall back-grouting material has low shrinkage, short setting time and high compressive strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of comprehensive utilization of solid waste resources, and specifically relates to an early-strength, low-shrinkage inert back-wall grouting material and a preparation method thereof. Background Art

[0002] In tunnel construction, the shield construction method using synchronous grouting technology has become the main construction method at present due to its excellent safety and economy. The synchronous grouting materials used in shield construction are mainly divided into active slurry containing cement and inert slurry without cement. In actual projects, both slurries are used according to the differences in on-site construction conditions. In comparison, inert slurry has the advantages of low cost and good construction performance, but it is also prone to the disadvantage of insufficient compensation for shrinkage. During and after hardening, volume shrinkage will occur, resulting in the loss of effective bonding between the grouting material and the rock wall, making it difficult to ensure the stability of tunnel construction. In actual projects, inert grouting materials are usually mixed with bentonite to improve the shrinkage of the grouting materials, but the effect is limited, and the addition of bentonite will reduce the strength of the grouting materials. Therefore, it is necessary to develop new inert grouting materials with low shrinkage. Summary of the invention

[0003] The purpose of the present invention is to provide an early-strength, low-shrinkage inert wall back-grouting material and a preparation method thereof. The inert wall back-grouting material has low shrinkage, short setting time and high compressive strength.

[0004] The present invention adopts the following technical scheme: an early-strength, low-shrinkage inert back-wall grouting material, which is composed of the following raw materials in weight content: 16% to 22% of molten iron desulfurization slag ultrafine powder, 2.1% to 2.3% of modifier, 5% to 11% of fly ash, 0.4% to 0.6% of water reducer, 3% to 5% of enhanced alkaline activator, 30% to 34% of river sand, 24% to 28% of water, 0.3% to 0.4% of reinforcing agent, 3% to 6% of desulfurization gypsum, and 2% to 5% of diatomaceous earth, and the total content of the raw materials is 100%.

[0005] Furthermore, it is composed of the following raw materials in weight content: 22% ultrafine powder of molten iron desulfurization slag, 2.3% modifier, 8% fly ash, 0.4% water reducer, 4% enhanced alkaline activator, 30% river sand, 25% water, 0.3% enhancer, 4% desulfurization gypsum, 4% diatomaceous earth, and the total content of raw materials is 100%.

[0006] Furthermore, the enhanced alkaline activator is a mixed activator of a water glass solution with a purity of 95% and an enhancer, and its modulus is 1.0-2.25.

[0007] Furthermore, the water reducing agent is a powdered polycarboxylic acid water reducing agent, and the water reducing rate is 25% to 30%.

[0008] Furthermore, the modifier is a silane coupling agent composite solution, which includes the following components in percentage by mass: 30% silane coupling agent, 65% acetone, and 5% water, and the silane coupling agent is KH-560.

[0009] Furthermore, the effective components of the hot metal desulfurization slag ultrafine powder are CaO 52.11%, SiO2 14.82%, Al2O3 5.61%, SO3 2.03%, and the specific surface area is 891m 2 / kg.

[0010] Furthermore, the desulfurized gypsum contains 93.97% CaSO4·2H2O and has a fineness of 400 meshes.

[0011] Furthermore, the enhancer is a composite chemical agent of sodium hydroxide and potassium hydroxide, wherein the mass ratio of potassium hydroxide to sodium hydroxide is 2:1.

[0012] The present invention also discloses a method for preparing the above-mentioned early-strength, low-shrinkage inert back-wall grouting material, which comprises the following steps:

[0013] Ultrafine powder of hot metal desulfurization slag, fly ash, diatomaceous earth and a modifier are placed in a magnetic stirrer and stirred and mixed at 120° C. to obtain a composite powder of modified ultrafine powder of hot metal desulfurization slag, diatomaceous earth and fly ash;

[0014] Add the enhancer to the alkaline stimulator, stir evenly, and let stand to room temperature to obtain an enhanced alkaline stimulator solution;

[0015] Mix the enhanced alkali-activated solution into water and add 80% of it into the mortar mixer;

[0016] Add the modified hot metal desulfurization slag ultrafine powder, diatomaceous earth, fly ash composite powder, water reducing agent, desulfurization gypsum and river sand into the mortar mixer and stir;

[0017] Add the remaining 20% ​​of the enhanced alkali excitation solution and stir to obtain the product.

[0018] Furthermore, the preparation of the molten iron desulfurization slag ultrafine powder is as follows:

[0019] The mesh number of the sieve frame is adjusted to 100, and the molten iron desulfurization slag is circulated and screened, and the undersize material is collected; the mesh number of the frame is 400, the undersize material is taken and placed at the feed port, and the material is circulated and screened to obtain a mixed material; the mesh number of the sieve frame is adjusted to 800, the mixed material is placed at the feed port, sieved, and the undersize material is taken to obtain ultrafine powder of molten iron desulfurization slag.

[0020] The beneficial effects of the present invention are as follows: 1. The grouting material added with the ultrafine powder of hot metal desulfurization slag can produce a slight expansion, which solves the disadvantage of insufficient compensation shrinkage capacity of the inert grouting material. In addition, the ultrafine powder of hot metal desulfurization slag can form a sulphoaluminate gelling system with fly ash and diatomite, improve the early strength of the grouting material, and have high compressive strength, so that the grouting material has a broad application prospect. 2. The reinforcing agent can synergistically stimulate the ultrafine powder of hot metal desulfurization slag, fly ash, and diatomite to achieve the purpose of the gelling material, shorten the setting time of the inert grouting slurry, and significantly improve the early and late strengths, overcoming the disadvantages of poor mechanical properties and long setting time of the inert slurry. 3. The addition of desulfurized gypsum can react with the ultrafine powder of hot metal desulfurization slag and fly ash to generate calcium sulfonate crystals, which can not only improve the early strength of the grouting material, but also fill in the gaps in the grouting material, improve the density of the material, have low shrinkage, and have micro-expansion, and are more suitable for the shield geological environment. It improves the environmental damage caused by desulfurized gypsum and has great significance for the application of solid waste resources. DETAILED DESCRIPTION

[0021] The present invention is described in detail below through specific implementation modes.

[0022] The invention discloses an early-strength and low-shrinkage inert back-wall grouting material, which is composed of the following raw materials in weight content: 16%-22% of molten iron desulfurization slag superfine powder, 2.1%-2.3% of modifier, 5%-11% of fly ash, 0.4%-0.6% of water reducer, 3%-5% of enhanced alkaline activator, 30%-34% of river sand, 24%-28% of water, 0.3%-0.4% of reinforcing agent, 3%-6% of desulfurization gypsum, 2%-5% of diatomaceous earth, and the total content of the raw materials is 100%.

[0023] It is composed of the following raw materials in weight content: 22% of ultrafine powder of molten iron desulfurization slag, 2.3% of modifier, 8% of fly ash, 0.4% of water reducer, 4% of enhanced alkaline activator, 30% of river sand, 25% of water, 0.3% of enhancer, 4% of desulfurization gypsum, 4% of diatomaceous earth, and the total content of raw materials is 100%.

[0024] The enhanced alkaline activator is a mixed activator of a water glass solution with a purity of 95% and an enhancer, and its modulus is 1.0-2.25.

[0025] The water reducing agent is a powdered polycarboxylic acid water reducing agent with a water reducing rate of 25% to 30%.

[0026] The modifier is a silane coupling agent composite solution, which includes the following components in percentage by mass: 30% of silane coupling agent, 65% of acetone, and 5% of water. The silane coupling agent is KH-560.

[0027] The effective components of hot metal desulfurization slag ultrafine powder are CaO 52.11%, SiO2 14.82%, Al2O3 5.61%, SO3 2.03%, and the specific surface area is 891m 2 / kg.

[0028] The content of CaSO4·2H2O in desulfurized gypsum is 93.97% and the mesh size is 400.

[0029] The enhancer is a composite chemical agent of sodium hydroxide and potassium hydroxide, wherein the mass ratio of potassium hydroxide to sodium hydroxide is 2:1.

[0030] The present invention also discloses a method for preparing the above-mentioned early-strength, low-shrinkage inert wall back-grouting material, which comprises the following steps:

[0031] The mesh number of the ball mill sieve frame is adjusted to 100, the molten iron desulfurization slag is placed at the feed inlet, and the sieve material is circulated for 75 minutes. The undersize material is collected at the discharge port, and the mesh number of the sieve frame is adjusted to 400. The undersize material is placed at the feed inlet, and the sieve material is circulated for 45 minutes to obtain a mixture. The mesh number of the sieve frame is adjusted to 800, and the mixture is placed at the feed inlet. The mixture is sieved for 30 minutes to obtain ultrafine powder of molten iron desulfurization slag;

[0032] Ultrafine powder of hot metal desulfurization slag, fly ash, diatomaceous earth and a modifier are placed in a magnetic stirrer and mixed at 120° C. for 15 minutes to obtain a composite powder of modified ultrafine powder of hot metal desulfurization slag, diatomaceous earth and fly ash;

[0033] Add the enhancer to the alkaline stimulator, stir evenly, and let stand to room temperature to obtain an enhanced alkaline stimulator solution;

[0034] Mix the enhanced alkali-activated solution into water and add 80% of it into the mortar mixer;

[0035] Add the modified hot metal desulfurization slag ultrafine powder, diatomaceous earth, fly ash composite powder, water reducer, desulfurization gypsum and river sand into the mortar mixer and stir slowly for 30 seconds;

[0036] Add the remaining 20% ​​enhanced alkali excitation solution and continue to stir slowly for 90 seconds to obtain the product.

[0037] The following are specific examples, wherein 100 g of an early-strength, low-shrinkage inert back-wall grouting material is prepared in each example.

[0038] Example 1

[0039] An early-strength, low-shrinkage inert back-wall grouting material is composed of the following raw materials by weight: 19g of molten iron desulfurization slag ultrafine powder, 2.2g of modifier, 8g of fly ash, 0.5g of water reducer, 4g of enhanced alkaline activator, 32g of river sand, 26g of water, 0.3g of reinforcing agent, 5g of desulfurization gypsum, and 3g of diatomaceous earth.

[0040] The particle size of the above river sand is 0.2mm to 0.5mm.

[0041] The enhanced alkaline activator is a mixed activator of a water glass solution with a purity of 95% and a modulus of 1.0 to 2.25 and an enhancer solution.

[0042] The water reducing agent is a powdered polycarboxylic acid high-efficiency water reducing agent, and the water reducing rate is between 25% and 30%.

[0043] The main components of the above-mentioned hot metal desulfurization slag ultrafine powder are CaO (52.11%), SiO2 (14.82%), Al2O3 (5.61%), SO3 (2.03%), and the specific surface area is 891m 2 / kg.

[0044] The main component of the above desulfurized gypsum is CaSO4·2H2O (93.97%), and the fineness is 400 meshes.

[0045] The main components of the above fly ash are SiO2 (53.97%), Al2O3 (31.15%), and Fe2O3 (4.16%).

[0046] The main component of the diatomaceous earth is SiO2 (94.36%), and the fineness is 10000.

[0047] The above-mentioned modifier is a silane coupling agent composite solution, which includes the following components in percentage by mass: 30% silane coupling agent, 65% acetone, and 5% water. The silane coupling agent is KH-560.

[0048] The enhancer is a composite chemical of sodium hydroxide and potassium hydroxide, wherein the mass ratio of potassium hydroxide to sodium hydroxide is (1-2):(2-1), the sodium hydroxide is analytically pure, and the potassium hydroxide is analytically pure.

[0049] The present invention also discloses a method for preparing the above-mentioned early-strength and low-shrinkage back-wall grouting material, comprising the following steps:

[0050] Adjust the mesh number of the ball mill sieve frame to 100, place the molten iron desulfurization slag at the feed inlet, circulate the sieve for 60 minutes, collect the undersized material at the discharge port, adjust the mesh number of the sieve frame to 400, take the undersized material and place it at the feed inlet, circulate the sieve for 60 minutes to obtain the mixture, adjust the mesh number of the sieve frame to 800, place the mixture at the feed inlet, sieve for 30 minutes to obtain the molten iron desulfurization slag ultrafine powder.

[0051] Ultrafine powder of hot metal desulfurization slag, fly ash, diatomaceous earth and a modifier are placed in a magnetic stirrer and mixed at 110° C. for 20 minutes to obtain a composite powder of modified ultrafine powder of hot metal desulfurization slag, diatomaceous earth and fly ash;

[0052] Add the enhancer to the alkaline stimulator, stir evenly, and let stand to room temperature to obtain an enhanced alkaline stimulator solution;

[0053] Mix the enhanced alkali-activated solution into water and add 80% of it into the mortar mixer;

[0054] Add the modified hot metal desulfurization slag ultrafine powder, diatomaceous earth, fly ash composite powder, water reducer, desulfurization gypsum and river sand into the mortar mixer and stir slowly for 35 seconds;

[0055] Add the remaining 20% ​​enhanced alkali excitation solution and continue to stir slowly for 85 seconds to obtain the product.

[0056] Example 2

[0057] The differences between this embodiment and embodiment 1 are listed below, and the contents not listed are the same.

[0058] An early-strength, low-shrinkage inert back-wall grouting material and a preparation method thereof are composed of the following raw materials by weight: 16 g of molten iron desulfurization slag ultrafine powder, 2.1 g of modifier, 11 g of fly ash, 0.5 g of water reducer, 5 g of enhanced alkaline activator, 30 g of river sand, 27 g of water, 0.4 g of reinforcing agent, 6 g of desulfurization gypsum, and 2 g of diatomaceous earth.

[0059] The enhancer is a composite chemical of sodium hydroxide and potassium hydroxide, wherein the ratio of potassium hydroxide to sodium hydroxide is 1:1, the sodium hydroxide is analytically pure, and the potassium hydroxide is analytically pure.

[0060] The present invention also discloses a method for preparing the above-mentioned early-strength and low-shrinkage back-wall grouting material, comprising the following steps:

[0061] Adjust the mesh number of the ball mill sieve frame to 100, place the molten iron desulfurization slag at the feed port, circulate and sieve the material for 75 minutes, collect the undersized material at the discharge port, adjust the mesh number of the sieve frame to 400, take the undersized material and place it at the feed port, circulate and sieve the material for 55 minutes to obtain the mixture, adjust the mesh number of the sieve frame to 800, place the mixture at the feed port, sieve the material for 20 minutes to obtain the ultrafine powder of molten iron desulfurization slag.

[0062] Ultrafine powder of hot metal desulfurization slag, fly ash, diatomaceous earth and a modifier are placed in a magnetic stirrer and mixed at 130° C. for 10 minutes to obtain a composite powder of modified ultrafine powder of hot metal desulfurization slag, diatomaceous earth and fly ash;

[0063] Add the enhancer to the alkaline stimulator, stir evenly, and let stand to room temperature to obtain an enhanced alkaline stimulator solution;

[0064] Mix the enhanced alkali-activated solution into water and add 80% of it into the mortar mixer;

[0065] Add the modified hot metal desulfurization slag ultrafine powder, diatomaceous earth, fly ash composite powder, water reducer, desulfurization gypsum and river sand into the mortar mixer and stir slowly for 60 seconds;

[0066] Add the remaining 20% ​​enhanced alkali excitation solution and continue to stir slowly for 60 seconds to obtain the product.

[0067] Example 3

[0068] The differences between this embodiment and embodiment 1 are listed below, and the contents not listed are the same.

[0069] An early-strength, low-shrinkage inert back-wall grouting material is composed of the following raw materials by weight: 20g of molten iron desulfurization slag ultrafine powder, 2.1g of modifier, 7g of fly ash, 0.6g of water reducer, 3g of enhanced alkaline activator, 34g of river sand, 27g of water, 0.3g of reinforcing agent, 3g of desulfurization gypsum, and 3g of diatomaceous earth.

[0070] The enhancer is a composite chemical of sodium hydroxide and potassium hydroxide, wherein the ratio of potassium hydroxide to sodium hydroxide is 2:1, the sodium hydroxide is analytically pure, and the potassium hydroxide is analytically pure.

[0071] The present invention also discloses a method for preparing the above-mentioned early-strength and low-shrinkage back-wall grouting material, comprising the following steps:

[0072] Adjust the mesh number of the ball mill sieve frame to 100, place the molten iron desulfurization slag at the feed port, circulate the sieve for 80 minutes, collect the undersized material at the discharge port, adjust the mesh number of the sieve frame to 400, take the undersized material and place it at the feed port, circulate the sieve for 45 minutes to obtain the mixture, adjust the mesh number of the sieve frame to 800, place the mixture at the feed port, sieve for 20 minutes to obtain the molten iron desulfurization slag ultrafine powder.

[0073] Ultrafine powder of hot metal desulfurization slag, fly ash, diatomaceous earth and a modifier are placed in a magnetic stirrer and mixed at 130° C. for 10 minutes to obtain a composite powder of modified ultrafine powder of hot metal desulfurization slag, diatomaceous earth and fly ash;

[0074] Add the enhancer to the alkaline stimulator, stir evenly, and let stand to room temperature to obtain an enhanced alkaline stimulator solution;

[0075] Mix the enhanced alkali-activated solution into water and add 80% of it into the mortar mixer;

[0076] Add the modified hot metal desulfurization slag ultrafine powder, diatomaceous earth, fly ash composite powder, water reducer, desulfurization gypsum and river sand into the mortar mixer and stir slowly for 45 seconds;

[0077] Add the remaining 20% ​​enhanced alkali excitation solution and continue to stir slowly for 75 seconds to obtain the product.

[0078] Example 4

[0079] The differences between this embodiment and embodiment 1 are listed below, and the contents not listed are the same.

[0080] An early-strength, low-shrinkage inert back-wall grouting material and a preparation method thereof are composed of the following raw materials in terms of mass content: 21 g of ultrafine powder of molten iron desulfurization slag, 2.2 g of a modifier, 5 g of fly ash, 0.4 g of a water reducer, 5 g of an enhanced alkaline activator, 31 g of river sand, 24 g of water, 0.4 g of a reinforcing agent, 6 g of desulfurized gypsum, and 5 g of diatomaceous earth.

[0081] The enhancer is a composite chemical of sodium hydroxide and potassium hydroxide, wherein the ratio of potassium hydroxide to sodium hydroxide is 1:1, the sodium hydroxide is analytically pure, and the potassium hydroxide is analytically pure.

[0082] This embodiment also discloses a method for preparing the above-mentioned early-strength, low-shrinkage back-wall grouting material, comprising the following steps:

[0083] The mesh number of the ball mill sieve frame is adjusted to 100, the molten iron desulfurization slag is placed at the feed port, the sieve material is circulated for 85 minutes, the undersize material is collected at the discharge port, the mesh number of the sieve frame is adjusted to 400, the undersize material is placed at the feed port, the sieve material is circulated for 45 minutes, a mixture is obtained, the mesh number of the sieve frame is adjusted to 800, the mixture is placed at the feed port, and the material is sieved for 20 minutes to obtain ultrafine powder of molten iron desulfurization slag;

[0084] Ultrafine powder of hot metal desulfurization slag, fly ash, diatomaceous earth and a modifier are placed in a magnetic stirrer and mixed at 120° C. for 15 minutes to obtain a composite powder of modified ultrafine powder of hot metal desulfurization slag, diatomaceous earth and fly ash;

[0085] Add the enhancer to the alkaline stimulator, stir evenly, and let stand to room temperature to obtain an enhanced alkaline stimulator solution;

[0086] Mix the enhanced alkali-activated solution into water and add 80% of it into the mortar mixer;

[0087] Add the modified hot metal desulfurization slag ultrafine powder, diatomaceous earth, fly ash composite powder, water reducer, desulfurization gypsum and river sand into the mortar mixer and stir slowly for 40 seconds;

[0088] Add the remaining 20% ​​enhanced alkali excitation solution and continue to stir slowly for 80 seconds to obtain the product.

[0089] Example 5

[0090] The differences between this embodiment and embodiment 1 are listed below, and the contents not listed are the same.

[0091] An early-strength, low-shrinkage inert back-wall grouting material and a preparation method thereof are composed of the following raw materials by weight: 22 g of molten iron desulfurization slag ultrafine powder, 2.3 g of modifier, 8 g of fly ash, 0.4 g of water reducer, 4 g of enhanced alkaline activator, 30 g of river sand, 25 g of water, 0.3 g of reinforcing agent, 4 g of desulfurized gypsum, and 4 g of diatomaceous earth.

[0092] The above-mentioned enhancer is a composite chemical agent of sodium hydroxide and potassium hydroxide, wherein the ratio of potassium hydroxide to sodium hydroxide is 2:1, the sodium hydroxide is analytically pure, and the potassium hydroxide is analytically pure.

[0093] This embodiment also discloses a method for preparing the above-mentioned early-strength, low-shrinkage back-wall grouting material, comprising the following steps:

[0094] The mesh number of the ball mill sieve frame is adjusted to 100, the molten iron desulfurization slag is placed at the feed inlet, and the sieve material is circulated for 75 minutes. The undersize material is collected at the discharge port, and the mesh number of the sieve frame is adjusted to 400. The undersize material is placed at the feed inlet, and the sieve material is circulated for 45 minutes to obtain a mixture. The mesh number of the sieve frame is adjusted to 800, and the mixture is placed at the feed inlet. The mixture is sieved for 30 minutes to obtain ultrafine powder of molten iron desulfurization slag;

[0095] Ultrafine powder of hot metal desulfurization slag, fly ash, diatomaceous earth and a modifier are placed in a magnetic stirrer and mixed at 110° C. for 20 minutes to obtain a composite powder of modified ultrafine powder of hot metal desulfurization slag, diatomaceous earth and fly ash;

[0096] Add the enhancer to the alkaline stimulator, stir evenly, and let stand to room temperature to obtain an enhanced alkaline stimulator solution;

[0097] Mix the enhanced alkali-activated solution into water and add 80% of it into the mortar mixer;

[0098] Add the modified hot metal desulfurization slag ultrafine powder, diatomaceous earth, fly ash composite powder, water reducer, desulfurization gypsum and river sand into the mortar mixer and stir slowly for 30 seconds;

[0099] Add the remaining 20% ​​enhanced alkali excitation solution and continue to stir slowly for 90 seconds to obtain the product.

[0100] In order to verify the effects of the components in the early-strength, low-shrinkage inert back-wall grouting material of the present invention, the following comparative examples were used for verification. In each comparative example, the amount of the inert back-wall grouting material prepared was 100 g.

[0101] Comparative Example 1

[0102] An inert back-wall grouting material is composed of the following raw materials by weight: 22g of molten iron desulfurization slag ultrafine powder, 2.3g of modifier, 8g of fly ash, 0.4g of water reducer, 4g of enhanced alkaline activator, 34g of river sand, 25g of water, 0.3g of enhancer, and 4g of diatomaceous earth.

[0103] The particle size of the river sand is 0.2mm to 0.5mm. The enhanced alkaline activator is a mixed activator of a water glass solution with a purity of 95% and a modulus of 1.0 to 2.25 and an enhancer solution. The water reducer is a powdered polycarboxylic acid high-efficiency water reducer with a water reduction rate of 25% to 30%. The main components of the above-mentioned molten iron desulfurization slag ultrafine powder are CaO (52.11%), SiO2 (14.82%), Al2O3 (5.61%), SO3 (2.03%), and the specific surface area is 891m 2 / kg. The main components of the fly ash are SiO2 (53.97%), Al2O3 (31.15%), and Fe2O3 (4.16%).

[0104] The main component of the diatomaceous earth is SiO2 (94.36%), and the fineness is 10000.

[0105] The above-mentioned modifier is a silane coupling agent composite solution, which includes the following components in percentage by mass: 30% silane coupling agent, 65% acetone, and 5% water. The silane coupling agent is KH-560.

[0106] The enhancer is a composite chemical of sodium hydroxide and potassium hydroxide, wherein the mass ratio of potassium hydroxide to sodium hydroxide is 2:1, the sodium hydroxide is analytically pure, and the potassium hydroxide is analytically pure.

[0107] This comparative example also discloses a method for preparing the above-mentioned early-strength, low-shrinkage back-wall grouting material, comprising the following steps:

[0108] The mesh number of the ball mill sieve frame is adjusted to 100, the molten iron desulfurization slag is placed at the feed inlet, and the sieve material is circulated for 75 minutes. The undersize material is collected at the discharge port, and the mesh number of the sieve frame is adjusted to 400. The undersize material is placed at the feed inlet, and the sieve material is circulated for 45 minutes to obtain a mixture. The mesh number of the sieve frame is adjusted to 800, and the mixture is placed at the feed inlet. The mixture is sieved for 30 minutes to obtain ultrafine powder of molten iron desulfurization slag;

[0109] Ultrafine powder of hot metal desulfurization slag, fly ash, diatomaceous earth and a modifier are placed in a magnetic stirrer and mixed at 110° C. The stirring time is 20 minutes to obtain a composite powder of modified ultrafine powder of hot metal desulfurization slag, diatomaceous earth and fly ash.

[0110] The enhancer is added into the alkaline activator, stirred evenly, and allowed to stand to room temperature to obtain an enhanced alkaline activating solution.

[0111] Mix the enhanced alkali-activated solution into water, take 80% of it and add it to the mortar mixer; add the modified hot metal desulfurization slag ultrafine powder, fly ash, diatomaceous earth mixed powder, water reducer and river sand into the mortar mixer and stir slowly for 30 seconds. Add the remaining 20% ​​of the enhanced alkali-activated solution and continue to stir slowly for 90 seconds to obtain the product.

[0112] Comparative Example 2

[0113] The differences between this comparative example and comparative example 1 are listed below, and the contents not listed are the same.

[0114] An inert back-wall grouting material is composed of the following raw materials by weight: 2.3g of modifier, 30g of fly ash, 0.4g of water reducer, 4g of enhanced alkaline activator, 30g of river sand, 25g of water, 0.3g of reinforcing agent, 4g of desulfurized gypsum, and 4g of diatomaceous earth.

[0115] The main component of desulfurized gypsum is CaSO4·2H2O (93.97%), and the mesh size is 400. The main components of fly ash are SiO2 (53.97%), Al2O3 (31.15%), and Fe2O3 (4.16%).

[0116] This comparative example also discloses a method for preparing the above-mentioned back-wall grouting material, comprising the following steps:

[0117] Fly ash, diatomaceous earth and a modifier are placed in a magnetic stirrer and mixed at 110° C. for 20 minutes to obtain a mixed powder of modified diatomaceous earth and fly ash;

[0118] Add the enhancer to the alkaline stimulator, stir evenly, and let stand to room temperature to obtain an enhanced alkaline stimulator solution;

[0119] Mix the enhanced alkali-activated solution into water and add 80% of it into the mortar mixer;

[0120] Add the mixed powder of modified fly ash and diatomaceous earth, desulfurized gypsum, water reducing agent and river sand into the mortar mixer and stir slowly for 30 seconds;

[0121] Add the remaining 20% ​​enhanced alkali excitation solution and continue to stir slowly for 90 seconds to obtain the product.

[0122] Comparative Example 3

[0123] The differences between this comparative example and comparative example 1 are listed below, and the contents not listed are the same.

[0124] An inert back-wall grouting material is composed of the following raw materials by weight: 22g of steel slag powder, 2.3g of modifier, 8g of fly ash, 0.4g of water reducer, 4g of enhanced alkaline activator, 30g of river sand, 25g of water, 0.3g of reinforcing agent, 4g of desulfurized gypsum, and 4g of diatomaceous earth.

[0125] The main components of the above-mentioned steel slag powder are CaO (54.17%), SiO2 (17.79%), Fe2O3 (9.65%), and MgO (6.23%), the porosity is 38.7%, and the water absorption rate is 2.25%.

[0126] The main component of the above desulfurized gypsum is CaSO4·2H2O (93.97%), and the fineness is 400 meshes.

[0127] This comparative example also discloses a method for preparing the above-mentioned back-wall grouting material, comprising the following steps:

[0128] The steel slag powder, fly ash, diatomaceous earth and the modifier are placed in a magnetic stirrer and mixed at 110° C. to 130° C. for 10 to 20 minutes to obtain a mixed powder of modified steel slag powder, diatomaceous earth and fly ash;

[0129] Add the enhancer to the alkaline stimulator, stir evenly, and let stand to room temperature to obtain an enhanced alkaline stimulator solution;

[0130] Mix the enhanced alkali-activated solution into water and add 80% of it into the mortar mixer;

[0131] Add the mixed powder of modified steel slag powder, fly ash, diatomaceous earth, desulfurized gypsum, water reducer and river sand into a mortar mixer and stir slowly for 30 seconds; add the remaining 20% ​​enhanced alkali-activated solution and continue stirring slowly for 90 seconds to obtain the product.

[0132] Comparative Example 4

[0133] The differences between this comparative example and comparative example 1 are listed below, and the contents not listed are the same.

[0134] An inert back-wall grouting material is composed of the following raw materials by weight: 22g bentonite, 2.3g modifier, 8g fly ash, 0.4g water reducer, 4g enhanced alkaline activator, 30g river sand, 25g water, 0.3g enhancer, 4g desulfurized gypsum, and 4g diatomaceous earth.

[0135] The main components of the bentonite are SiO2 (71.54%), Al2O3 (17.61%), Na2O (3.16%), and CaO (2.18%). The main component of the desulfurized gypsum is CaSO4·2H2O (93.97%), and the fineness is 400 mesh.

[0136] This comparative example also discloses a method for preparing the above-mentioned back-wall grouting material, comprising the following steps:

[0137] Fly ash, diatomaceous earth and a modifier are placed in a magnetic stirrer and mixed at 110° C. for 20 minutes to obtain a mixed powder of modified fly ash and diatomaceous earth;

[0138] Add the enhancer to the alkaline stimulator, stir evenly, and let stand to room temperature to obtain an enhanced alkaline stimulator solution;

[0139] Mix the enhanced alkali-activated solution into water and add 80% of it into the mortar mixer;

[0140] Add the mixed powder of modified fly ash and diatomaceous earth, bentonite, desulfurized gypsum, water reducer and river sand into a mortar mixer and stir slowly for 30 seconds; add the remaining 20% ​​enhanced alkali-activated solution and continue stirring slowly for 90 seconds to obtain the product.

[0141] Comparative Example 5

[0142] The differences between this comparative example and comparative example 1 are listed below, and the contents not listed are the same.

[0143] An inert back-wall grouting material is composed of the following raw materials by weight: 22g of ultrafine powder of molten iron desulfurization slag, 8g of fly ash, 0.4g of water reducer, 4g of enhanced alkaline activator, 32.3g of river sand, 25g of water, 0.3g of reinforcing agent, 4g of desulfurization gypsum, and 4g of diatomaceous earth.

[0144] The main component of the above desulfurized gypsum is CaSO4·2H2O (93.97%), and the fineness is 400 meshes.

[0145] This comparative example also discloses a method for preparing the above-mentioned back-wall grouting material, comprising the following steps:

[0146] The mesh number of the ball mill sieve frame is adjusted to 100, the molten iron desulfurization slag is placed at the feed inlet, and the sieve material is circulated for 75 minutes. The undersize material is collected at the discharge port, and the mesh number of the sieve frame is adjusted to 400. The undersize material is placed at the feed inlet, and the sieve material is circulated for 45 minutes to obtain a mixture. The mesh number of the sieve frame is adjusted to 800, and the mixture is placed at the feed inlet. The mixture is sieved for 30 minutes to obtain ultrafine powder of molten iron desulfurization slag;

[0147] Add the enhancer to the alkaline stimulator, stir evenly, and let stand to room temperature to obtain an enhanced alkaline stimulator solution;

[0148] Mix the enhanced alkali-activated solution into water and add 80% of it into the mortar mixer;

[0149] Add ultrafine powder of hot metal desulfurization slag, fly ash, water reducing agent, desulfurization gypsum, diatomaceous earth and river sand into the mortar mixer and stir slowly for 30 seconds;

[0150] Add the remaining 20% ​​enhanced alkali excitation solution and continue to stir slowly for 90 seconds to obtain the product.

[0151] Comparative Example 6

[0152] The differences between this comparative example and comparative example 1 are listed below, and the contents not listed are the same.

[0153] An inert back-wall grouting material is composed of the following raw materials by weight: 22g of molten iron desulfurization slag ultrafine powder, 2.3g of modifier, 8g of fly ash, 0.4g of water reducer, 4g of enhanced alkaline activator, 30g of river sand, 25g of water, 0.3g of enhancer, 4g of desulfurization gypsum, and 4g of diatomaceous earth.

[0154] The main component of the above desulfurized gypsum is CaSO4·2H2O (93.97%), and the fineness is 400 meshes.

[0155] The above-mentioned modifier is a silane coupling agent composite solution, which includes the following components in percentage by mass: 30% silane coupling agent, 65% acetone, and 5% water. The silane coupling agent is KH-570.

[0156] This comparative example also discloses a method for preparing the above-mentioned back-wall grouting material, comprising the following steps:

[0157] The mesh number of the ball mill sieve frame is adjusted to 100, the molten iron desulfurization slag is placed at the feed inlet, and the sieve material is circulated for 75 minutes. The undersize material is collected at the discharge port, and the mesh number of the sieve frame is adjusted to 400. The undersize material is placed at the feed inlet, and the sieve material is circulated for 45 minutes to obtain a mixture. The mesh number of the sieve frame is adjusted to 800, and the mixture is placed at the feed inlet. The mixture is sieved for 30 minutes to obtain ultrafine powder of molten iron desulfurization slag;

[0158] Ultrafine powder of hot metal desulfurization slag, fly ash, diatomaceous earth and a modifier are placed in a magnetic stirrer and mixed at 120° C. for 15 minutes to obtain a composite powder of modified ultrafine powder of hot metal desulfurization slag, diatomaceous earth and fly ash;

[0159] Add the enhancer to the alkaline stimulator, stir evenly, and let stand to room temperature to obtain an enhanced alkaline stimulator solution;

[0160] Mix the enhanced alkali-activated solution into water and add 80% of it into the mortar mixer;

[0161] Add the modified hot metal desulfurization slag ultrafine powder, diatomaceous earth, fly ash composite powder, water reducer, desulfurization gypsum and river sand into the mortar mixer and stir slowly for 30 seconds;

[0162] Add the remaining 20% ​​enhanced alkali excitation solution and continue to stir slowly for 90 seconds to obtain

[0163] The back-wall grouting liquid in the embodiment and the comparative example was tested according to the technical requirements of the Technical Specification for Application of Synchronous Grouting Materials for Shield Tunneling Method T-CECS 563-2018, and the results are shown in Table 1:

[0164] Table 1 Performance of back-wall grouting materials

[0165]

[0166]

[0167] By comparing the product performance in Example 5 with that in Comparative Example 1, it is found that the 3d strength of the product without desulfurized gypsum is reduced by 38%, and the 28d consolidation shrinkage rate is reduced by 23% compared with the product with desulfurized gypsum, which significantly improves the early strength and shrinkage resistance of the grouting material.

[0168] By comparing the product performance in Example 5 with that in Comparative Example 2, it is found that the 3d compressive strength of the product without the addition of ultrafine iron molten desulfurization slag powder is reduced by 62%, the 28d compressive strength is reduced by 67%, and the 28d consolidation shrinkage rate is increased by 499%. After the grouting material is added with the molten iron desulfurization slag, the performance of various aspects can be significantly improved.

[0169] Comparing the product performance in Example 5 with that in Comparative Example 3, it is found that the product added with ultrafine powder of molten iron desulfurization slag has a 28d consolidation shrinkage rate reduced by 41% compared with the product added with fine steel slag powder, which effectively improves the shrinkage resistance of the grouting material.

[0170] By comparing the product performance in Example 5 with that in Comparative Example 4, it is found that the 3d compressive strength of the product added with bentonite is reduced by 48%, and the 28d compressive strength is reduced by 61% compared with the product added with ultrafine powder of molten iron desulfurization slag. Compared with the traditional expansive material bentonite, the grouting material added with molten iron desulfurization slag has better mechanical properties and excellent shrinkage resistance.

[0171] Comparing the product performance in Example 5 with that in Comparative Example 5, it is found that the 3d compressive strength of the product without the modifier is reduced by 26%, and the 28d compressive strength is reduced by 20% compared with the product with the modifier. Therefore, KH-560 has a modifying effect on the mechanical properties of the grouting material.

[0172] Comparing the product performance in Example 5 with that in Comparative Example 6, it is found that the 3d compressive strength of the product added with KH-570 is reduced by 25% and the 28d compressive strength is reduced by 16% compared with the product added with KH-560. Therefore, KH-570 has no modifying effect on the mechanical properties of the grouting material.

[0173] The 28d consolidation shrinkage rate of the grouting material commonly used in the art is 1.27%. By comparing Example 5 with this, it is found that the 28d compressive strength is reduced by 63.8%.

[0174] The hot metal desulfurization slag ultrafine powder used in each embodiment of the present invention is hot metal desulfurization slag, which is iron-containing slag produced during the desulfurization pretreatment process, and is a metallurgical bulk solid waste. Hot metal desulfurization slag ultrafine powder has the properties of mineral powder due to the special process different from steel slag production; at the same time, hot metal desulfurization slag ultrafine powder contains a certain amount of sulfate, so an appropriate amount of hot metal desulfurization slag ultrafine powder can form a sulphoaluminate gelling system with fly ash and diatomaceous earth to improve the early strength of the grouting material; at the same time, the f-CaO and f-MgO in the hot metal desulfurization slag ultrafine powder can undergo hydration reaction to form a micro-expanded crystalline hydrate calcium sulfonate, which can reduce the shrinkage of the material and improve the density of the material within a certain range.

[0175] The silane coupling agent in the silane coupling agent composite solution has an amorphous organic functional group. Under the action of the dispersant acetone, the amorphous organic functional group is caused to evenly adhere to the surface of inorganic materials such as hot metal desulfurization slag ultrafine powder, fly ash, diatomaceous earth, etc., which can improve the surface properties of the material, cause the surface of the modified inorganic material to have hydrophobicity, reduce the thickness of the water film between the reactant particles during the hydration process, and thus control the hydration reaction process, that is, promote the hydration reaction of hot metal desulfurization slag ultrafine powder, fly ash, and diatomaceous earth to form a sulphoaluminate gelling system in the early stage, and inhibit the hydration reaction of the hot metal desulfurization slag ultrafine powder in the later stage to reduce the generation of expansion products.

[0176] The fineness of diatomite is 10000 mesh, with the characteristics of large specific surface area and good dispersibility. Diatomite, fly ash and hot metal desulfurization slag ultrafine powder are all inorganic materials, and they have good compatibility. Therefore, diatomite can be combined with fly ash and hot metal desulfurization slag ultrafine powder to form sulphoaluminate, which can improve the early strength of the structural interface and the overall density.

[0177] Desulfurized gypsum is a kind of sulfate, which can react with Ca(OH)2 produced by the hydration reaction of ultrafine iron molten desulfurized slag powder and aluminum-containing substances in fly ash to form calcium sulfonate crystals. It can not only form a skeleton structure and improve the early strength of the grouting material, but also fill in the gaps in the grouting material to increase the density of the material.

Claims

1. An early-strength, low-shrinkage inert back-wall grouting material, characterized in that: It is composed of the following raw materials by weight: 16%~22% of ultrafine powder of molten iron desulfurization slag, 2.1%~2.3% of modifier, 5%~11% of fly ash, 0.4%~0.6% of water reducer, 3%~5% of enhanced alkaline activator, 30%~34% of river sand, 24%~28% of water, 0.3%~0.4% of enhancer, 3%~6% of desulfurization gypsum, 2%~5% of diatomaceous earth, and the total content of raw materials is 100%; The enhanced alkaline activator is a mixed activator of a water glass solution with a purity of 95% and an enhancer, and its modulus is 1.0-2.25; The modifier is a silane coupling agent composite solution, which includes the following components in percentage by mass: 30% silane coupling agent, 65% acetone, and 5% water, and the silane coupling agent is KH-560; The enhancer is a composite chemical agent of sodium hydroxide and potassium hydroxide, wherein the mass ratio of potassium hydroxide to sodium hydroxide is 2:

1.

2. An early-strength, low-shrinkage inert back-wall grouting material as claimed in claim 1, characterized in that: It is composed of the following raw materials in weight content: 22% ultrafine powder of molten iron desulfurization slag, 2.3% modifier, 8% fly ash, 0.4% water reducer, 4% enhanced alkaline activator, 30% river sand, 25% water, 0.3% enhancer, 4% desulfurization gypsum, 4% diatomaceous earth, and the total content of raw materials is 100%.

3. An early-strength, low-shrinkage inert back-wall grouting material as claimed in claim 2, characterized in that: The water reducing agent is a powdered polycarboxylic acid water reducing agent with a water reducing rate of 25% to 30%.

4. An early-strength, low-shrinkage inert back-wall grouting material as claimed in claim 3, characterized in that: The effective components of the hot metal desulfurization slag ultrafine powder are CaO 52.11%, SiO2 14.82%, Al2O3 5.61%, SO3 2.03%, and the specific surface area is 891m 2 / kg.

5. An early-strength, low-shrinkage inert back-wall grouting material as claimed in claim 4, characterized in that: The desulfurized gypsum contains 93.97% CaSO4•2H2O and has a mesh size of 400.

6. A method for preparing an early-strength, low-shrinkage inert back-wall grouting material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following: Ultrafine powder of hot metal desulfurization slag, fly ash, diatomaceous earth and a modifier are placed in a magnetic stirrer and stirred and mixed at 120° C. to obtain a composite powder of modified ultrafine powder of hot metal desulfurization slag, diatomaceous earth and fly ash; Add the enhancer to the alkaline stimulator, stir evenly, and let stand to room temperature to obtain an enhanced alkaline stimulator; Mix the enhanced alkaline activator into water and add 80% of it into the mortar mixer; Add the modified hot metal desulfurization slag ultrafine powder, diatomaceous earth, fly ash composite powder, water reducing agent, desulfurization gypsum and river sand into the mortar mixer and stir; Add the remaining 20% ​​enhanced alkaline activator and stir to obtain the product.

7. The method for preparing an early-strength, low-shrinkage inert back-wall grouting material according to claim 6, characterized in that: The preparation of the ultrafine powder of molten iron desulfurization slag is as follows: The mesh number of the sieve frame is adjusted to 100, and the molten iron desulfurization slag is circulated and screened, and the undersize material is collected; the mesh number of the frame is 400, the undersize material is taken and placed at the feed port, and the material is circulated and screened to obtain a mixed material; the mesh number of the sieve frame is adjusted to 800, the mixed material is placed at the feed port, sieved, and the undersize material is taken to obtain ultrafine powder of molten iron desulfurization slag.

Citation Information

Patent Citations

  • Industrial waste residue multi-component composite shield tunnel wall post-grouting material and preparation method thereof

    CN111205060A

  • C25-grade alkali-activated silicon-aluminum all-solid waste concrete and preparation method thereof

    CN112851156A